Evaluasi Program Aplikasi Sistem Informasi Desa Terintegrasi (SRIGATI) di Kantor Desa Widodaren Kabupaten Ngawi - Widyaningrum, Tahlia Aninda Yulia; Winarti; Suhita, Damayanti (Solidaritas, 2024)
The implementation of e-government can enhance efficiency, transparency, and public participation. In line with this, the Ngawi Regency government has started implementing e- government at the village level through the Integrated Village Information System (SRIGATI) application. The aim of this research is to describe the success of the Integrated Village Information System (SRIGATI) application program through the evaluation of the SRIGATI application program at the Widodaren Village Office, Ngawi Regency. The SRIGATIapplication is used by the community to access information about the village, such as events and activities in Widodaren Village, or to access Widodaren Village data.The success of the implementation of the Integrated Village Information System (SRIGATI) application is measured through the Nurcholis evaluation indicators, which consist of input, process, output, and outcome. This research uses a descriptive method with a qualitative approach, and data collection techniques include interviews, documentation, and observation. The data analysis techniques used are data condensation, data presentation, and conclusion drawing.The results of this research can be summarized as follows The implementation of the Integrated Village Information System (SRIGATI) application at the Widodaren Village Office is not yet satisfactory. In the input indicator, the implementation of the SRIGATI application can be considered quite good, although there are still many things that need improvement, such as the need for direct socialization to the Widodaren Village community. In the process indicator, it is considered good, but there are challenges with the operator during the operation of the SRIGATI application. In the output indicator, the results are not yet satisfactory because the community is not satisfied with the implementation of the SRIGATI application at the Widodaren Village Office. Meanwhile, in the outcome indicator, the impact of the SRIGATI application is perceived as not yet significant.